COVID-19 Crisis, Ownership and Bank Efficiency in Emerging Market Economies: An Empirical Study of Vietnam - Vu THT; Nguyen V; Le PT; Ngo T (Institute of Economics of the Ural Branch of RAS, 2025)
Research on banking efficiency is abundant, yet studies typically focus on agency theory, which yields mixed findings, or analyse the impact of COVID-19 on performance without accounting for ownership differences. This paper investigates the effect of the COVID-19 pandemic on the efficiency of the Vietnamese banking system, with a focus on different ownership types. Using data from 28 Vietnamese banks over 2016 to 2022, a bootstrap variant of data envelopment analysis is employed to assess efficiency, and the Simar and Zelenyuk (2007) subgrouping test is used to compare bank performance by ownership and pandemic effects. Results show that private banks are significantly less efficient in providing intermediation services and generating profits, while state-owned and foreign banks perform better. Overall, Vietnamese banks demonstrated resilience during the pandemic, but private banks lagged behind, indicating a need for targeted oversight to enhance sector efficiency. Regression analyses incorporating control variables provide further insights. Credit growth has little impact on performance, nonperforming loans improve operational efficiency, larger banks are more efficient, and a higher deposits-to-assets ratio negatively affects efficiency. These findings suggest the need for policy measures such as careful assessment of bank performance, targeted efficiency interventions for private banks, balancing risk and efficiency in lending, promoting bank growth, and diversifying funding sources. The results may also offer lessons for other emerging economies, including ASEAN and Latin American countries.
Keywords: COVID-19 crisis; bank efficiency; ownership; data envelopment analysis (DEA); bootstrap; Vietnam